EU’s Foreign Policy towards the Arab Gulf since 2008 Is there any? - Tahboub, Naser (Dirasat: Human and Social Sciences, 2021)
In 1988 a Cooperation Agreement between the European Union and the Gulf Cooperation Council was signed, with the goal of strengthening and deepening economics and political ties between the two. The following year negotiations for the signing of a free trade agreement were initiated; in 2008 they were halted and never resumed. Since then, the EU didn’t seem able to set a comprehensive and tailor-made foreign policy towards its partners in the Arab Gulf, due to both contingent and structural problems and an overall asymmetry in the level of integration of the two institutions. Nowadays, the Arab Gulf and the political events unfolding there, have revived the EU’s necessity of adopting a broad policy in shaping its relations with monarchies there. Nevertheless, the EU’s external action is damaged by the resilience of national bilateral relations regarding strategic trade flows and diplomatic activities, hampering its common stand on sensible concerns.